A new predictive hypothesis for phase difference reflection in GHz - Elmutasim, Imadeldin Elsayed; Izzeldin Ibrahim, Mohamed Abdelaziz; Mohamad Shaiful, Abdul Karim (MDPI, 2023)
Wave phase difference is a fundamental property that characterises the relative behaviour of transmitted signals. It has significant roles in signal wave analysis and in interpreting various propagation phenomena, which are crucial when designing wireless links and various applications in signal processing techniques, optics, and acoustics. This study investigated the concept of phase difference significance based on high frequencies (i.e., 1.0, 2.4, 10.0, and 20.0 GHz). Several phase difference models and their shortcomings were reviewed to emphasise the need for greater accuracy and precision in quantifying phase differences. The outcomes revealed that 1 GHz contributed to the lowest phase difference among the other frequencies. A constructive signal may be deployed to provide a better link build-up. Overall, determining the importance of phase difference in GHz and identifying the signal attitude substantially contribute to the advancement of wave analysis, while simultaneously encouraging further exploration in this domain.